Factors influencing physicians’ antimicrobial prescribing decisions: A systematic review of qualitative studies - Reali, Savannah; Kwang, Yee Chin; Cho, Jin‐Gun; Alffenaar, Jan‐Willem; Aslani, Parisa (British journal of clinical pharmacology, 2025)
Inappropriate and overuse of antimicrobials is increasing antimicrobial resistance. Understanding physicians' antimicrobial decision‐making is essential for developing interventions to optimize prescribing. The aim of this review was to identify the factors that influence physicians' antimicrobial prescribing decisions. A systematic literature search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Embase, Medline and Scopus were searched from 2014 onwards using three key concepts: antimicrobial, prescribing and attitude. The search identified 11 038 articles for review. Studies were included if they used qualitative methods and obtained data directly from physicians. Factors influencing antimicrobial prescribing were extracted and categorized into physician‐related, patient‐related, medication‐ and condition‐related, and external factors. A model of the antimicrobial prescribing process was created to illustrate how these factors influence decision‐making. Fifty‐three articles from 23 countries met the inclusion criteria. Forty factors influencing antimicrobial prescribing were identified, with the most common being time pressures, patient/carer demand for antimicrobials, diagnostic uncertainty, clinical experience, and the use of evidence‐based guidelines and diagnostic tests. The harm to the patient and the physician of underprescribing were considered to outweigh the potential population harm of antimicrobial resistance due to overprescribing. Antimicrobial decision making is a complex process influenced by many different types of factors at each point in the prescribing journey. Awareness of these factors is vital for the success of interventions aiming to optimize antimicrobial prescribing. Future interventions should investigate how to balance individual and population harm whilst considering the individual factors that influence prescribing decisions.